Enhanced Beidou user equipment access authentication protocol based on location key - Jin CAO; Qiuyu BU; Yuanyuan YANG; Hui LI; Qiao LIU; Maode MA (Tongxin xuebao)
In order to solve the shortcomings of the existing Beidou user equipment access solutions such as prolonged authentication, and in response to the need of user privacy protection, a user equipment access authentication protocol based on location key was proposed, which realized the mutual authentication and session key negotiation between entities.Combining Beidou’s location information and master key to form a two-factor, the proposed protocol solved the security problem of the master key leaking due to the equipment being captured during the authentication process to some extent.The proposed protocol can meet different security requirements through the verification of the Scyther formal tool.Compared with other similar schemes, it has better performance overhead, and is suitable for Beidou satellite navigation system with limited node resources.